Case Report and Review of Literature: Thyroid Metastases From Breast Carcinoma - Wang, Yichao; Zhou, Shengliang; Yu, Boyang; Zhou, Ping; Zhu, Jingqiang; Wei, Tao; Li, Zhihui (Frontiers in Endocrinology, 2021)
Rationale The thyroid is a rare site for distant metastases from breast carcinoma. The incidence of thyroid metastases in fine needle aspiration biopsy (FNAB) was less than 0.2%. Patient concerns We report a case of 54-year-old woman with a history of breast carcinoma presented with diffuse scattered microcalcifications in thyroid and enlarged bilateral cervical lymph nodes detected on ultrasound (US). Physical examination of the patient revealed firm and enlarged thyroid lobes. Diagnoses FNAB and immunohistochemistry (IHC) of the thyroid lesion confirmed the thyroid metastases from breast cancer. Interventions and Outcomes Due to the comorbidities of breast carcinoma metastases to the right axillary, cervical lymph nodes and left chest wall, the patient received chemotherapy. After a follow-up of 19 months, the patient was alive without any new distant metastases. Lessons Our case highlights that thyroid metastases should be considered in a patient combined with thyroid lesions and a history of breast carcinoma. IHC played an important role in differentiating thyroid metastases from primary thyroid cancer.